Unraveling the impact of arsenic on the redox response of peanut plants inoculated with two different Bradyrhizobium sp. strains. (November 2020) - Peralta, Juan Manuel; Travaglia, Claudia N.; Romero-Puertas, María C.; Furlan, Ana; Castro, Stella; Bianucci, Eliana
Abstract: Arsenic (As) can be present naturally in groundwater from peanut fields, constituting a serious problem, as roots can accumulate and mobilize the metalloid to their edible parts. Understanding the redox changes in the legume exposed to As may help to detect potential risks to human health and recognize tolerance mechanisms. Thirty-days old peanut plants inoculated with Bradyrhizobium sp. strains (SEMIA6144 or C-145) were exposed to a realistic arsenate concentration, in order to unravel the redox response and characterize the oxidative stress indexes. Thus, root anatomy, reactive oxygen species detection by fluorescence microscopy and, ROS histochemical staining along with the NADPH oxidase activity were analyzed. Besides, photosynthetic pigments and damage to lipids and proteins were determined as oxidative stress indicators. Results showed that at 3 μM As V, the cross-section areas of peanut roots were augmented; NADPH oxidase activity was significantly increased and O2 ˙¯and H2 O2 accumulated in leaves and roots. Likewise, an increase in the lipid peroxidation and protein carbonyls was also observed throughout the plant regardless the inoculated strain, while chlorophylls and carotenes were increased only in those inoculated with Bradyrhizobium sp. C-145. Interestingly, the oxidative burst, mainly induced by the NADPH oxidase activity, and the consequent oxidative stress was strain-dependent and organ-differential. Additionally, As modifies the root anatomy, acting as a possibly first defense mechanism against the metalloid entry. All these findings allowed us to conclude that the redox response of peanut is conditioned by the rhizobial strain, which contributes to the importance of effectively formulating bioinoculants for this crop. Graphical abstract: Graphical Abstract . A proposed model to explain the impact of a realistic arsenate concentration on the peanut- Bradyrhizobium sp. (strains SEMIA6144 or C-145) symbiotic interaction. Plant maintains or increase their photosynthetic pigment content as a possible strategy to sustain carbon fixation. Additionally, the main root increases its cross section area as a potential first restriction mechanism against metalloid entry. In leaves and roots, NADPH oxidase activity is increased along with the accumulation of superoxide anion (O2 ˙¯) and hydrogen peroxide (H2 O2 ). Consequently, the oxidative burst can be associated with lipid and protein damages, as revealed by the increase in TBARS and protein carbonyls content, respectively. The extent of oxidative stress is modulated by the tolerance to As of the rhizobial strain. Image 1 Highlights: The redox response of the peanut-bradyrhizobia symbiosis exposed to As V is unveiled. Root anatomy changes are the first defense mechanism against As entry. The NADPH activity in peanut organs is modulated by the rhizobial tolerance. Oxidative stress is Bradyrhizobium sp. strain-dependent and organ-differential.